Modelling the Significance of Value-Belief-Norm Theory in Predicting Solid Waste Management Intention and Behavior - Al Mamun, Abdullah; Hayat, Naeem; Masud, Muhammad Mehedi; Makhbul, Zafir Khan Mohamed; Jannat, Taslima; Salleh, Mohd Fairuz Md. (Frontiers in Environmental Science, 2022)
Urbanisation and rapid use of natural resources worldwide lead to a massive increase in the solid waste produced daily. The processing of solid waste is significantly lower than the production of solid waste. Sustainable solid waste processing requires collective efforts and a change in the general public mindset to reduce and effectively process solid waste. The current work aims to interpret the intention and behaviour to mitigate the climatic issue of solid waste management among Malaysian adults under the premises of value-belief-norm (VBN) framework, which was extended with the inclusion of social norms. This study adopted cross-sectional design and collected quantitative data through online survey from a total of 1571 household heads in Malaysia. Data was analysed with partial least square-structure equation modelling (PLS-SEM) technique, given that the data were non-normal. Other relevant common method bias analyses were conducted to evaluate the influence of common method variance. The analysis findings demonstrated that the biospheric and altruistic values were essential for promoting the ecological worldview among the individuals. Following the VBN framework, the ecological worldview instigates the awareness of consequences, which facilitate the ascription of responsibility to perform corrective actions for the climate. Moreover, ecological worldview, awareness of consequences, and ascription of responsibility result in the personal norms towards the pro-climate behaviours. The social and personal norms effectively nurture the intention to engage in solid waste management practices. The VBN framework provides a guideline to promote the intention and behaviour to adopt effective solid waste management practice, while education and public policy could harness public beliefs and norms to engage in pro-climatic behaviours.